2019
DOI: 10.1002/ange.201908052
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Promoted 1,3‐Dithiolium‐4‐olates–Alkyne Cycloaddition

Abstract: Reported here is the reactivity of mesoionic 1,3‐dithiolium‐4‐olates towards strained alkynes, leading to thiophene cycloaddition products. In the process, the potential of these dipoles towards orthogonal reaction with azides, allowing efficient double ligation reactions, was discovered. A versatile process to access benzo[c]thiophenes, in an unprecedented divergent fashion, was developed and provides a new entry to unconventional polyaromatic thiophenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…In 2019, Taran, Audisio, and co‐workers reported a strain‐promoted cycloaddition reaction between 1,3‐dithiolium‐4‐olates (DTOs) and cyclooctyne or benzyne derivatives [20] . The reaction occurs through a [3+2] cycloaddition to form a bridged intermediate, which then undergoes a retro‐Diels–Alder reaction to afford the thiophene or benzo[c]thiophene cycloadduct and COS as byproduct.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Taran, Audisio, and co‐workers reported a strain‐promoted cycloaddition reaction between 1,3‐dithiolium‐4‐olates (DTOs) and cyclooctyne or benzyne derivatives [20] . The reaction occurs through a [3+2] cycloaddition to form a bridged intermediate, which then undergoes a retro‐Diels–Alder reaction to afford the thiophene or benzo[c]thiophene cycloadduct and COS as byproduct.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Taran and coworkers showed that 1,3-dithiolium-4-olates (DTO) could be an alternative H 2 S/COS donor when reacting with strained alkynes. [28] However, the release of H 2 S was not demonstrated. More recently, inspired by Taran's work, Liang and coworkers developed a mitochondrial targeting H 2 S/COS donor by introducing a diphenylamino substituent on DTO.…”
Section: Introductionmentioning
confidence: 96%
“…Over the past decade, several bioorthogonal [3 + 2] cycloaddition (32CA) reactions [1][2][3][4][5][6][7][8][9][10][11][12][13][14] with structural functionalisation of cycloalkynes have provided a reliable alternative to the use of toxic metal catalysts. Strainpromoted 32CA (SP-32CA) reactions are rapid, tuneable reactions for bioorthogonal labelling.…”
Section: Introductionmentioning
confidence: 99%
“…Strainpromoted 32CA (SP-32CA) reactions are rapid, tuneable reactions for bioorthogonal labelling. [4] One of the best characterised bioorthogonal SP-32CA reactions, the strain-promoted azide-alkyne cycloaddition [5] (SPAAC), is used to design more reactive cycloalkynes. The dibenzoannulated cyclooctyne (DIBO) skeleton was first developed by Ning et al [6] as a reactive probe to undergo metal-free 32CA reactions with azido-containing amino acids and saccharides (see Scheme 1).…”
Section: Introductionmentioning
confidence: 99%